Abnormal Low-Frequency Oscillations Reflect Abnormal Eye Movement and Stereovision in Patients With Comitant Exotropia - Chen, Juan; Jin, Han; Zhong, Yu-Lin; Huang, Xin (Frontiers in Human Neuroscience, 2021)
Abstract Background: Concomitant exotropia (CE) patients is accompanied by abnormal eye movements and stereovision. However, the neurophysiological mechanism of impaired eye movements and stereo vision is still unclear. Purpose:the purpose of our study is to investigate spontaneous neural activity changes in CE patients using amplitude of low-frequency fluctuations (ALFF) method and machine learning method. Material and Methods:Twenty-one patients CE and Twenty-one healthy controls (HCs) underwent resting-state magnetic resonance imaging scans. The ALFF and fALFF values were chosen as classification features using a machine learning method. Results: Compared to the HC group, CE patients had significant decreased ALFF values in the right angular(ANG)/middle occipital gyrus (MOG)/middle temporal gyrus (MTG) and bilateral supplementary motor area(SMA)/precentral gyrus (PreCG). Meanwhile, CE patients showed significant increased fALFF values in the left putamen (PUT) and decreased fALFF values in the right ANG/MOG. Moreover, CE patients showed a decreased FC between the right ANG/MOG/MTG and the bilateral calcarine (CAL)/lingual(LING) and increased FC between the left PUT and the bilateral cerebellum 8/9 (CER 8/9). The SVM classification reach a total accuracy of 93% and 90% and the area under curve（AUC）of 0.93 and 0.90 based on ALFF and fALFF values. Conclusion: our result highlighted that CE patients had abnormal brain neural activities including middle occipital gyrus (MOG), supplementary motor area(SMA)/precentral gyrus (PreCG), which might reflect the neural mechanism of eye movements and stereo vision dysfunction in CE patients. Moreover, ALFF and fALFF could be a sensitive biomarker for distinguishing patients with CE from HCs.